Evaluating the Role of Social Media in Tourist Decision-Making - Andelina S., Lidia Juniati; Safitri, Dania; Rahmasari, Anissa Aulia; Faza, Luthfi Ghani (SABA: Journal of Tourism Research, 2025)
This study examines the influence of Instagram as a promotional tool on tourist decision-making, using Kiara Artha Park in Bandung as a case study. A quantitative survey was conducted with 122 valid respondents, and data were analysed using simple linear regression. The findings reveal a strong positive relationship between Instagram-based promotions and tourist decision-making, with 66.7% of the variance in decision-making explained by promotional activities on Instagram. Respondents agreed that Instagram is informative, visually appealing, and helpful in planning visits. However, while Instagram significantly influences interest and intent to visit, actual visit behaviour shows more variation. These results align with prior research emphasising Instagram's role in destination branding. Limitations include the single-location focus and demographic skew toward younger users. Future studies should explore diverse destinations, include more variables, and apply longitudinal methods to assess long-term behavioural impacts of social media on tourism.